2012
DOI: 10.1088/1742-6596/402/1/012042
|View full text |Cite
|
Sign up to set email alerts
|

Morphology diagrams forA2Bcopolymer melts: real-space self-consistent field theory

Abstract: The standard Gaussian model for block copolymermelts M W Matsen -Stability of the fcc structure in block copolymer systems Makiko Nonomura -SCFT simulation and SANS study on spatial distribution of solvents in microphase separation induced by a differentiating non-solvent in a semi-dilute solution of an ultra-high-molecular-weight block copolymer K Ando, T Yamanaka, S Okamoto et al. Abstract. Morphology diagrams for A2B copolymer melts are constructed using real-space self-consistent field theory (SCFT). In pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…30 Quantitative comparison of our experimental results to Figure 2 in ref 42 and Figure 5 in ref 32 shows discrepancies. A similar real-space SCFT study 33 for conformationally symmetric nonlinear block copolymers shows the same. In particular, for an estimated value of χN = 54 for the PSPI 2 molecules studied by us, all of these studies predict a lamellar morphology (even for Φ PS = 74%), while experimentally, a gyroid morphology is found.…”
Section: Macromoleculessupporting
confidence: 53%
See 4 more Smart Citations
“…30 Quantitative comparison of our experimental results to Figure 2 in ref 42 and Figure 5 in ref 32 shows discrepancies. A similar real-space SCFT study 33 for conformationally symmetric nonlinear block copolymers shows the same. In particular, for an estimated value of χN = 54 for the PSPI 2 molecules studied by us, all of these studies predict a lamellar morphology (even for Φ PS = 74%), while experimentally, a gyroid morphology is found.…”
Section: Macromoleculessupporting
confidence: 53%
“…For a reduced value of χN = 30, used in our SCFT calculations, an excellent agreement with these studies is observed, and the sample is found to be close to the cylinder−gyroid boundary. Similarly, the PS 2 PI sample at χN = 30 and Φ PS = 70% is predicted 32,33,42 to be close to the sphere−cylinder boundary. Our SCFT calculations incorporating conformational asymmetry as presented in Figure 11 show elongated spheres, which confirm qualitative agreement with these previous studies.…”
Section: Macromoleculesmentioning
confidence: 83%
See 3 more Smart Citations